1995
DOI: 10.1002/star.19950471005
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Starch Acetate

Abstract: Acetylation of native hydrolyzed and oxidized, maize starch has been studied. The different factors affecting acetylation process were investigated. These factors include liquor ratio, acetic anhydride, perchloric acid concentration, reaction time and temperature. Also investigated were characterization and application of the acetylated starches in textile warp sizing. The acetyl content increases to reach a maximum and then decreases on increasing either liquor ratio or perchloric acid concentration. Also it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 21 publications
5
39
0
2
Order By: Relevance
“…RE (%) was calculated according to Khalil et al (1995) as DS × anhydroglucose (mol)/acetic anhydride (mol) × 100%.…”
Section: Determination Of Reaction Efficiency (Re)mentioning
confidence: 99%
“…RE (%) was calculated according to Khalil et al (1995) as DS × anhydroglucose (mol)/acetic anhydride (mol) × 100%.…”
Section: Determination Of Reaction Efficiency (Re)mentioning
confidence: 99%
“…The overall reaction rate equation: (12) where k" is the overall reaction rate constant: (13) Equation (10) is described as follows: (14) where R is radius of anhidroglucose particle at time t (which is an unknown quantity). This can be eliminated with the help of mass of anhidroglucose and fractional conversion of anhidroglucose.…”
Section: Hydrolysis Of Starch Acetatementioning
confidence: 99%
“…Based on the starch acetate SEM analysis [10], it has been proven that the granula size of the acetylated starch is larger than the native one, thus, the fractional conversion of anhidroglucose in terms of weight of anhidroglucose is: (16) (17) Substitution Equation (17) to Equation (14), gives: (18) 3. Materials and Methods…”
Section: Hydrolysis Of Starch Acetatementioning
confidence: 99%
See 1 more Smart Citation
“…Ohishi, Kasai, Shimada & Hatae (2007) reported that the swelling power and solubility indexes of starch pastes with and without acetic acid increase with increase in heating temperature from 60 ⁰C and with the swelling behaviour of starch mainly due the swelling of amylopectin (Tsai, Li & Lii, 1997). Starches can be esterified with an acid, however, according to Khalil, Hashem & Hebeish (1995), the esterification of starch also depends on the heating temperature. Starch acetates, which are very useful industrially, are known to be formed by the action of acetic acid on starch with acetyl content of starch acetate elevated with an increase in the heating temperature.…”
Section: Phmentioning
confidence: 99%